Modelagem numérica de tanques de armazenamento térmico aplicada a sistemas de refrigeração por adsorção - Adolfo, Cristian (2015)
The environmental issues and the search for renewable and cheaper resources are encouraging the development of new air conditioner types. One of these models that can substitute the most usual nowadays is the adsorption air conditioner system, which does not need a vapor compressor and demands only a hot and a cold source to work. This hot source can easily be supplied by thermal waste or solar energy. However, the fact that solar energy varies throughout the day implies using a thermal storage system and an auxiliary heat source. Those have to be carefully designed in order to guarantee the maximum performance for the available solar energy. This text presents the development of the software SimAds, which employs numerical routines to solve the heating flow problem that occurs inside the adsorber bed during regeneration. The results given by SimAds are applied as boundary conditions in the thermal storage tank analysis of an adsorption air conditioner system. This study was carried out numerically evolving the Finite Volume Method, with physical and mathematical equations validated by S. Ievers’ (2009) work. The results showed that the storage tank's thermal stratification is higher between 2 p.m. and 5 p.m. in the afternoon, keeping lower levels during the rest of the day. The energy fraction demanded by the air conditioner's hot water circuit supplied by solar energy was find as 70%. The main conclusion shows that changing the tank inlet's height could increase the thermal performance of the storage system, principally in problems with more than one water inlet and transient temperatures.